Current Management of Post-radical Prostatectomy Urinary Incontinence - Rahnama'i, Mohammad S.; Marcelissen, Tom; Geavlete, Bogdan; Tutolo, Manuela; Hüsch, Tanja (Frontiers in Surgery, 2021)
Prostate cancer is the second most common cancer in men worldwide. Radical prostatectomy and radiation beam therapy are the most common treatment options for localized prostate cancer and have different associated complications. The etiology of post prostatectomy incontinence is multifactorial. There is evidence in the literature that anatomic support and pelvic innervation are important factors in the etiology of post-prostatectomy incontinence. Among the many surgical and technical factors proposed in the literature, extensive dissection during surgery, damage to the neurovascular bundle and the development of postoperative fibrosis have a substantial negative impact on the continence status of men undergoing RP. Sparing of the bladder neck and anterior, and possibly posterior, fixation of the bladder-urethra anastomosis are associated with better continence rates. Overactive bladder syndrome (OAB) is multifactorial and the exact role of prostate surgery in the development of OAB is still under debate. There are several variables that could contribute to detrusor overactivity. Detrusor overactivity in patients after radical prostatectomy has been mainly attributed to a partial denervation of the bladder during surgery. However, together with bladder denervation, other hypotheses, such as the urethrovesical mechanism, have been described. Although there is conflicting evidence regarding the importance of conservative treatment after post-prostatectomy urinary incontinence, pelvic floor muscle training (PFMT) is still considered as the first treatment choice. Duloxetin,, either alone or in combination with PFMT, may hasten recovery of urinary incontinence but is often associated with severe gastrointestinal and central nervous side effects. However, neither PFMT nor duloxetine may cure male stress urinary incontinence. The therapeutic decision and the chosen treatment option must be individualized for each patient according to clinical and social factors. During the recent years, the development of new therapeutic choices such as male sling techniques provided a more acceptable management pathway for less severe forms of urinary incontinence related to radical prostatectomy. Following this perspective, technological improvements and the emergence of new dedicated devices currently create the premises for a continuously positive evolution of clinical outcomes in this particular category of patients.